Perbandingan Tata Kelola Bank Syariah Murni Versus Bank Syariah Yang Didirikan Oleh Bank Umum - Tania, Atika Lusi (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
A study in Pakistan showed that there were significant differences between Islamic banks and Islamic banking established commercial banks on the Board of Directors and Syariah Advisory Council (Shahzad, 2014). In Indonesia, there is a purely Islamic banks set by the agency that had been principled sharia from the beginning, such as Bank Muamalat. However thee are Islamic banks established by commercial banks, such as Bank Syariah Mandiri, BRI Syariah and others.Using a sample of Bank Syariah Mandiri (BSM) and Bank Muamalat, the purpose of this paper is going to compare the reporting of governance between the two banks to determine whether or not there are differences in the practice of governance.The results show that, there are two major things that is different from the two banks, namely, foundation and CG policies and principles of CG. Runway and Bank Syariah Mandiri CG policy is not based on the Law of the Republic of Indonesia No. 21 Year 2011 on the Financial Services Authority and Sharia Supervisory Board Fatwa-Majelis Ulama Indonesia. Then the CG principle difference is the Bank Syariah Mandiri there is no principle of Concern Attitude (Social Awareness).